Dose-Dependent Effects of Insulin-Like Growth Factor 1 in the Aged Olfactory Epithelium - Ueha, Rumi; Kondo, Kenji; Ueha, Satoshi; Yamasoba, Tatsuya (Frontiers in Aging Neuroscience, 2018)
Background: Olfaction is known to be impaired by aging. We hypothesized that insulin-like growth factor-1 (IGF-1) administered at an appropriate dose could prevent age-induced negative effects on olfactory receptor neurons (ORNs). We explored the effects of low- and high-dose administration of IGF-1 on the ORN cell system in aged mice and investigated the involvement of the cellular mechanisms of IGF-1 in the regeneration of ORNs in aged mice. Methods: We subcutaneously administered recombinant human IGF-1 (rhIGF-1) to 16-month-old male mice over 56 days, and then examined the histological effects of rhGF-1 on cellular composition, cell proliferation, and cell death in the aged olfactory epithelium (OE), by comparing among saline-treated and low- and high-dose rhIGF-1-treated mice. Results: Low-dose rhIGF-1 administration increased the numbers of olfactory progenitors, immature ORNs, and mature ORNs in the OE, despite an increase in Cas3+ apoptotic cells. Notably, high-dose rhIGF-1 administration increased the numbers of only immature ORNs, not olfactory progenitors and mature ORNs, with a concurrent increase in apoptotic cells. Conclusion: Our data suggest that in aged mice, IGF-1 administered at an appropriate dose could increase the number of mature ORNs and further human studies may contribute to the development of treatments for aging-related olfactory impairment.